Fatal voyage - Reichs, Kathy (New York : Scribner, 2001)
After a fatal airline crash in the mountains of North Carolina, Dr. Temperance Brennan heads to the site to help identify the victims, but the discovery of body parts that do not belong to any registered passenger leads the investigation into a dangerous confrontation.
Keywords: Mystery fiction